(untitled) (Philology, 2022)
Abstract. In my study I examine the political and poetic changes in Hungary around 1968. The way in which Hungarian cultural politics tried to control literary life after the 1956 revolution and then changed this, partly out of necessity and partly because of accumulated tensions, from 1968 onwards, should be instructive for the international academic community. A little-studied question is how the political changes might have been related to the changes in poetry at that time, and I will try to answer this question in my study. I find that the response of Hungarian poets to political repression was both an ironic rejection of the role of the missionary poet and the inclusion of neo-avant-garde solutions expressing freedom in formal and linguistic terms in their poetic toolkit. My research required both a historical and a literary historical perspective. I began by describing the social constraints that led the political leadership to decide to relax censorship on literary life from 1968, and as a result, what was allowed to be published and what was still banned. Then I will show what poetic innovations the texts that were finally published brought to Hungarian literature.